Load Balanced Cross Layer Based Multipath Routing in Mobile Adhoc Network - J.Jean Justus, M. Anuradha, A.Sheryl Oliver (International Journal of Advanced Science and Technology, 2019)
Multipath routing in Mobile Ad-Hoc Network (MANET) usually results in end to end delay and overload in nodes. It is quite difficult to resolve these issues, but it can be reduced by implementing the cross-layered multi-path routing technique we propose in this paper. The initial step involves setting the optimal or better route using the cross-layer metric parameter, followed by sorting the cross-layered metric in descending order. The cross-layer metric is calculated using Expected Transmission Time, residual energy and the load balancing factor of the network. To balance the load, the primary and secondary paths are assessed by calculating the bandwidth that is available. This allows the network to split the data into parts and transmit these parts over the primary and secondary paths. Apart from this being a superior load balancing procedure, this technique avoids congestion during transmission. The success of this technique has been further validated by the findings of the simulation results.